VD_FINDINFO Arrêt / 2013 / 159 vom 2. April 2013 - VD Tribunal cantonal (2013)
TUTELLE, REJET DE LA DEMANDE, AFFECTION PSYCHIQUE | 14 al. 1 Tit. fin. CC, 14a Tit. fin. CC, 390 al. 1 ch. 1 CC, 398 CC, 450 CC